Correlation Between Length of Reference and Severity in Head Injury Patients in Emergency Installation Ulin Hospital Banjarmasin - Novia Heriani; Fenny N. Wahyuni (UrbanGreen, 2019)
One factor in the success of handling head injuries is the speed and accuracy of handling. The purpose of this study was to determine the relationship between the length of time of referral and the severity of head injury patients in Emergency Department of Ulin Hospital Banjarmasin. The research method was observational correlation with a cross sectional approach, the sample was head injury patients treated in the emergency room at Ulin District Hospital Banjarmasin as many as 52 people. Data were analyzed using the Spearman-Rho test. The results showed that patients with a referral time ≤ 1 hour 100% had a mild severity. Patients with a length of referral time >1 hour experienced moderate severity (41.2%), severe (35.3%), serious (17.6%), and mild (5.9%). There was a significant correlation between the length of time of referral and the severity of head injury patients and the strength of the correlation was strong.